History of Archaeological Research of Ancient Halych (from the Middle of the 19th to the End of the 20th Century) - Volodymyr Baran (Українознавство, 2016)
The article examines the history of the archaeological research of ancient Halych from the middle of the 19th to the end of the 20th century. Whereas ancient Halych was one of the leading cultural centers of Kyiv Rus, its studying will help us to show the place of Ukraine and Ukrainians in global ethno-cultural processes.